2004
DOI: 10.1002/mame.200300224
|View full text |Cite
|
Sign up to set email alerts
|

N,N‐Dimethylformamide Additions to the Solution for the Electrospinning of Poly(ε‐caprolactone) Nanofibers

Abstract: Summary: Additives that exhibit polyelectrolyte behavior such as N,N‐dimethylformamide (DMF) may improve the electrospinning characteristics of viscoelastic polymer solutions. DMF additions to the solution lead to extensive jet splaying, thereby reducing the fiber diameter significantly. Nanofibrous structures with diameters of the order of 150 nm can be produced by the addition of about 10 vol.‐% DMF to the solvent (chloroform). DMF additions also yield a narrow, unimodal distribution of fibers, compared to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
95
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(101 citation statements)
references
References 15 publications
4
95
0
2
Order By: Relevance
“…[34][35][36] It has also been reported that the bending instability of polymeric jet is increased when solvents with high dielectric constant are used, resulting in an increased deposition area, the enlargement of the jet path favoring the reduction of fiber size. 37 XRD spectra showed the characteristic (110), (111), (200), and (210) reflections of the orthorhombic crystal structure of PCL, 16,38 as pictured in Figure 4. Thus, electrospinning of PCL seems not to induce significant modifications of its crystal structure.…”
Section: Discussionmentioning
confidence: 99%
“…[34][35][36] It has also been reported that the bending instability of polymeric jet is increased when solvents with high dielectric constant are used, resulting in an increased deposition area, the enlargement of the jet path favoring the reduction of fiber size. 37 XRD spectra showed the characteristic (110), (111), (200), and (210) reflections of the orthorhombic crystal structure of PCL, 16,38 as pictured in Figure 4. Thus, electrospinning of PCL seems not to induce significant modifications of its crystal structure.…”
Section: Discussionmentioning
confidence: 99%
“…DMF is not a solvent for PCL but it has a high dielectric constant and could enhance electrospinning. Many studies showed that DMF help during the electrospinning and the formation of electrospun fibers [Lee et al, 2003;Hsu and Shivkumar, 2004].…”
Section: Methodsmentioning
confidence: 99%
“…Chloroform is most often applied as solvent for electrospinning PCL but produces rather microfibres instead of nanofibres as the diameters are typically 3 to 5 µm [15,17]. Other relatively highly toxic solvents such as dimethylformamide (DMF), tetrafluoroethylene, methylene chloride, dichloroethane and pyridine have been reported as well [4,6,[18][19][20][21][22]. Some of them allow for nanofibres with diameters in the nanoscale range but in none of the reported systems attention was given to the stability nor the reproducibility of the electrospinning process.…”
Section: Introductionmentioning
confidence: 99%